Analisis kebijakan pendidikan Islam pada Sekolah Umum di SMA/SMK - Marfu’ah, Nurry; M, Amril (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This research aims to explore more deeply the Islamic education policy in public schools, especially at the SMA / SMK level where the implementation of Islamic Religious Education in public schools is based on curriculum and lesson plans and focuses on learning outcomes. This research uses the literature study method. Data collection techniques were obtained from the library in the form of books, journals, and relevant conference proceedings, especially those related to Islamic education policies in public schools, especially at the senior high school/ vocational high school level. The research concludes that Islamic education policy in high school/vocational schools in Indonesia needs to focus on the integration of Islamic values in a curriculum that is balanced with general education. This can be done by strengthening the learning of morals, fiqh, and Islamic history, as well as providing space for students to develop critical and creative skills. In addition, teacher training in pedagogical approaches that are inclusive and based on Islamic values is essential to create a conducive learning environment.